Basics and principles of Algeria’s foreign policy and its African dimension (1962-1994( - abdelali, ibrahim (Journal of Social Sciences and Humanities, 2023)
Algerian diplomacy was dedicated to serving the country and the interests of the people, seeking to devote regional and international cooperation for the benefit of the peoples of the region and the world, and supporting the liberal approach in all its forms. Since Algeria regained its independence, it has adopted a set of principles that defined the parameters of its foreign policy, which is loyal to the principles of the glorious November 1 Revolution. It also worked hard to confirm the continuity of its revolutionary principles, as its efforts focused on dealing with the field of African brotherhood through its permanent endeavors to decolonize, liberate all African peoples, achieve more unity and solidarity among the countries of the continent, and protect its sovereignty, territorial integrity, and independence. Supporting efforts to maintain its economic independence by representing it and defending its interests in international forums and organizations.